2016
DOI: 10.1038/srep25698
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiles and pathways of genes in sugarcane leaf at elongation stage in response to drought stress

Abstract: Water stress causes considerable yield losses in sugarcane. To investigate differentially expressed genes under water stress, a pot experiment was performed with the sugarcane variety GT21 at three water-deficit levels (mild, moderate, and severe) during the elongation stage and gene expression was analyzed using microarray technology. Physiological parameters of sugarcane showed significant alterations in response to drought stress. Based on the expression profile of 15,593 sugarcane genes, 1,501 (9.6%) genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 54 publications
7
59
1
Order By: Relevance
“…The categories most expressed in the two cultivars and at all water-deficit times were binding and catalytic, followed by the categories cellular process, metabolic process, cell, and cell part. Our results agree with those obtained by Li et al (2016) who analyzed the expression of genes in only one drought-tolerant sugarcane cultivar (GT21) using microarray technology. The most expressed categories were the cell, cell part, organelle, cellular component organization, cellular process, catalytic activity, and binding.…”
Section: Sequence Annotation and Degs In Response To Prolonged Water supporting
confidence: 82%
See 2 more Smart Citations
“…The categories most expressed in the two cultivars and at all water-deficit times were binding and catalytic, followed by the categories cellular process, metabolic process, cell, and cell part. Our results agree with those obtained by Li et al (2016) who analyzed the expression of genes in only one drought-tolerant sugarcane cultivar (GT21) using microarray technology. The most expressed categories were the cell, cell part, organelle, cellular component organization, cellular process, catalytic activity, and binding.…”
Section: Sequence Annotation and Degs In Response To Prolonged Water supporting
confidence: 82%
“…Although these authors had subjected plants at 5 months of age to the water-deficit condition (total moisture content of 9 ± 2%), the response was only determined at 3, 7, and 9 days after stress application. These categories were the most representative in the cultivar tolerant to short-term water deficit (Li et al, 2016) and the two cultivars tolerant and sensitive to prolonged water deficit of this study (30, 60, and 90 days). These observations suggest that either the genes belonging to these categories are involved in basic events that are essential for the maintenance of sugarcane, regardless of its tolerant/sensitive nature, or the modulation of expression of these genes in one or the other cultivar is responsible for the different characteristics when subjected to water deficit.…”
Section: Sequence Annotation and Degs In Response To Prolonged Water mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . () reported a significant decrease in GA 3 content in droughted plants, it is therefore possible that exposure of droughted plants to GA 3 led to a recovery of RWC and chlorophyll content. Cutler et al .…”
Section: Resultsmentioning
confidence: 97%
“…Global analysis of transcripts altered by mild drought treatment in maize showed upregulation of genes involved in photosynthesis (Avramova et al ., ). Transcriptomic experiments in sugarcane treated with mild, moderate or severe drought stresses indicated that F v / F m decreased as water stress increased, with the most highly represented pathway categories being biosynthesis of secondary metabolites (Li et al ., 2016a). Tiling array analysis of Brachypodium seedlings treated with mild drought stress revealed that the stress did not change the expression level of genes related to cell division, despite the fact that leaf growth was decreased (Verelst et al ., ).…”
Section: Discussionmentioning
confidence: 99%